Nature-based solutions for flood mitigation in Canadian urban centers: A review of the state of research and practice - Ali Zoghi; Émilie Bilodeau; Muhammad Naveed Khaliq; Yeowon Kim; Jean-Luc Martel; Jennifer Drake (Journal of Hydrology: Regional Studies, 2025)
Study region: Canadian urban regions. Study focus: This paper examines nature-based solutions (NBS) for urban flood mitigation, assessing various practices such as bioretention cells, green roofs, permeable pavements, and rainwater harvesting in the context of Canadian cities. New hydrological insights for the region: The findings reveal that NBS are increasingly recognized as effective tools for managing urban stormwater and improving flood resilience. However, there is a significant gap between research and practice, with many municipalities still in the pilot project phase. Challenges include lack of region-specific design guidelines, especially for cold climates, and insufficient long-term performance and monitoring data. The paper highlights the need for more studies on assessing NBS effectiveness in northern regions, which remain under-researched. Additionally, the integration of NBS with traditional grey infrastructure is critical to maximizing flood mitigation benefits. The review also identifies the importance of developing cost-effective strategies and improved modeling tools to support the broader implementation of NBS. Future research should focus on evaluating NBS combinations, understanding their adaptive capacity in a warming climate, and addressing data gaps to bridge the divide between academic findings and practical applications of NBS.